The insertion of soft, soft-hard and hards technologies on the management of the care by the nurses of a university hospital- preview note - Rocha, Tatiana; Abrahão, Ana Lucia (Online Brazilian Journal of Nursing, 2007)
It is a research Project of the Pos-Graduation Strictu Senso - Professional Master’s -Assistant Nursing- Degree program of the Aurora de Afonso Costa Nursing School/UFF, Niterói/ Rio de Janeiro. Using the concept of technology developed by Merhy (1997) will be analysed the process of work of the nurse, trying to identify the use of the those technologies on the management of the care. This research will be done on a university hospital in the State of Rio de Janeiro. It is exploratory study with a qualitative approach, the data will be collected by a half-structuralized interview and a participant observation, being analysed by analysis of content of Bardin.